Saccadic Oscillations After Donepezil Administration in Patients with Dementia: Time Course and Clinical Correlates - Ileok Jung; Ji-Soo Kim; Moon-Ho Park (Journal of Eye Movement Research, 2026)
Donepezil, a cholinesterase inhibitor widely used in dementia, can be associated with saccadic oscillations (SO), but their time course and clinical relevance are unclear. In this prospective observational study, 18 patients with dementia underwent video-oculography at baseline (V0), one month (V1), and three months (V2) after initiation or dose escalation of donepezil. SO were counted over a single 30 s recording during visual fixation and in darkness, expressed as events/30 s. Dizziness was assessed with the Dizziness Handicap Inventory (DHI) and the Vestibular Disorders Activities of Daily Living (VADL) scale. Timepoints were compared using the Wilcoxon signed-rank test, and within-patient associations by repeated-measures correlation (rmcorr). SO with fixation increased from a median of 0.0 (interquartile range 0.0–1.0) events/30 s at V0 to 13.5 (7.2–15.8) at V1 (unadjusted p = 0.008, adjusted p = 0.023), then declined, but the difference from baseline lost statistical significance after multiple-comparison adjustment at V2 (6.5 [0.0–11.5]; unadjusted p = 0.031, adjusted p = 0.063). SO without fixation did not change (all p > 0.12). On rmcorr, SO without fixation was associated with the VADL (r = 0.59, p = 0.005) but neither measure was associated with the DHI. A transient, fixation-specific increase in SO was observed, peaking at one month and only partially resolved by three months; it correlated with functional disability rather than subjective handicap, suggesting that video-oculography warrants further study as a potential pharmacodynamic correlate of cholinergic drug effect in dementia.